Influence of operating parameters on the fate and removal of three estrogens in a laboratory-scale AAO system - Zhang, Zhaohan (Water science and technology : a journal of the International Association on Water Pollution Research, 2015)
A laboratory-scale anaerobic-anoxic-oxic (AAO) process was constructed to investigate the influence of hydraulic residence time (HRT) and sludge retention time (SRT) on the removal and fate of estrone (E1), 17β-estradiol (E2) and 17α-ethinylestradiol (EE2), and their removal mechanisms in a biological treatment system. In an HRT range of 5-15 h, the highest removal efficiencies for E1, E2 and EE2 were obtained at an HRT of 8 h, with values of 91.2, 94.6 and 81.5%, respectively. When the SRT was increased from 10 to 20 d, all three estrogen removal efficiencies stayed above 80%, while the optimal SRT for each estrogen was different. The contribution of each tank for removal of the three estrogens was in the order of aerobic tank>anoxic tank>anaerobic tank. The optimal HRT and SRT for the removal of both the three estrogens and nutrients were 8 h and 15d, respectively. At this condition, respectively, about 50.7, 70.1 and 11.3% of E1, E2 and EE2 were biodegraded, 28.8, 17.2 and 50% were accumulated in the system, 8.3, 5.4 and 17.3% were discharged in the effluent, and 12.2, 7.3 and 20.34% were transported into excess sludge. It indicated that biodegradation by sludge microorganisms was the main removal mechanism of E1 and E2, while adsorption onto sludge was the main mechanism for EE2 removal